The Effect of External Pressure, Ineffective Monitoring, Auditor Change, and Collusion on Financial Statement Fraud: (Empirical Study on Mining and Real Estate and Property Companies Listed on the IDX in 2019-2022) - Maulana, Raihan; Zarefar, Arumega; Diyanto, Volta (Riau International Conference on Economics, Business and Accounting, 2025)
Fraud according to The Institute of Internal Auditors (IIA) is any illegal act characterized by fraud, concealment, or breach of trust. This study aims to test and analyze whether External Pressure, Ineffective Monitoring, Auditor Change, and Collusion have an effect on Financial Statement Fraud. The population of this study is Mining and Real Estate Companies and properties listed on the Indonesia Stock Exchange (IDX) in 2019-2022. Samples were determined using purposive sampling. Testing this hypothesis uses multiple linear regression analysis conducted with the help of the SPSS 26 program. The results of this study show that external pressure reviewed based on the perspective of debt owned by companies has an influence on financial statement fraud. Meanwhile, ineffective monitoring, auditor turnover, and collusion show that they have an influence on financial statement fraud. It is hoped that the company’s management will be more careful in taking the right steps to prepare financial statements accurately, in order to avoid misstatements. The results of this research can also be used by companies as a source of information in decision-making, especially related to the integrity of financial statements, to improve the company’s performance and prospects in the future.